Use of splinting in traumatized primary teeth: A systematic review of case reports (Research, Society and Development, 2023)
The aim of this study was to explore the use of splinting in the management of traumatized primary dentition in case reports published in the literature. Systematic searches were performed in the main health databases to identify case reports (a) with children presenting trauma in primary teeth, and (b) those that described any outcomes related to the use of splints in the management of traumatized primary teeth. The stages of study selection, data extraction and risk of bias analysis were performed. Descriptive data analysis was described. The reporting of information from this review was based on the PRISMA 2020 guidelines. Of the total number of studies initially found (n=246), eight were case reports. Outcomes of splint immobilization in primary teeth with luxation (intrusion, extrusion, and lateral displacement), intra-alveolar root fracture and/or alveolar fracture were reported. All case reports described splinting as a viable technique for immobilizing traumatized primary teeth, regardless of the type of traumatic dental injury (TDIs) and splinting technique used. Only case report verified the effectiveness of the splinting in the management of dentoalveolar trauma and demonstrated the clinical effectiveness of the contentive approach. Based on low evidence studies with a moderate risk of bias, it was observed that the use of splints for the management of alveolar bone fractures and intrusive root fractures, and in specific cases of teeth with lateral luxation, can bring additional benefits to the dento-alveolar health of traumatized primary teeth.